Garden Festivals in Bolestraszyce - Wójcik-Popek, Agnieszka (Zakład Architektury Krajobrazu, Wydział Biologiczno-Rolniczy, Uniwersytet Rzeszowski, 2018)
In the previous year, the 7th Garden Festival in Bolestraszyce was already held. It is an annual event that brings together Polish garden enthusiasts and creators, teachers and young landscape architecture adepts, and even primary school representatives. Festivals have been organized since 2011 by the Arboretum and the Department of Physiography in Bolestraszyce, near Przemyśl. It has been initiated thanks to the funding from the Ministry of Culture and National Heritage. The festival is surrounded by the substantive care of the Landscape Architecture Association, the Association of Polish Landscape Architects, the Polish Nurserymen Association and the Polish Dendrological Society. Show gardens are an unusual variety of gardens – they serve to present the latest trends in the art of space arrangement and present, popularize new plant varieties. In recent years, they have also gained a wider educational function, often referring to environmental problems or various socio-cultural issues.

W poprzednim roku odbył się już VII Festiwal Ogrodowy w Bolestraszycach. Jest to wydarzenie skupiające rokrocznie polskich miłośników i twórców ogrodów, nauczycieli i młodych adeptów architektury krajobrazu, a nawet przedstawicieli szkół podstawowych. Festiwale organizowane są od 2011 przez Arboretum i Zakład Fizjografii w Bolestraszycach koło Przemyśla. Inicjatywę rozpoczęto dzięki dofinansowaniu ze środków Ministra Kultury i Dziedzictwa Narodowego. Festiwal jest otoczony opieką merytoryczną Stowarzyszenia Architektury Krajobrazu, Stowarzyszenia Polskich Architektów Krajobrazu, Związku Szkółkarzy Polskich i Polskiego Towarzystwa Dendrologicznego. Ogrody pokazowe są nietypową odmianą ogrodów – służą przedstawieniu najnowszych trendów w sztuce aranżacji przestrzeni oraz prezentują i popularyzują nowe odmiany roślin. W ostatnich latach zyskały także szerszą funkcję edukacyjną, często odnosząc się do problemów ochrony środowiska czy różnorodnych kwestii społeczno-kulturowych.
Keywords: show gardens; educational gardens; theme gardens; education in landscape architecture; ogrody pokazowe; ogrody edukacyjne; ogrody tematyczne